Analisis Produktivitas Kegiatan Promosi terhadap Brand Awareness Isp X - Singgih, Moses Laksono; Prasetyo, Panji Dwi (Jurnal Teknik Industri, 2008)
Products which have a good brand awareness will get long-term strategic advantages and one way of creating brand awareness is by promotion activities. This research tries to find out the efficiencies of promotion activities by comparing the number of sales with the promotional expenses. Beside that, a survey assigned to customers to collect informations about the most known promotion media in order to get informations about the most effective promotion media. To assure good qualities of the product promoted, the same survey also run to collect informations about differences between customer’s importances and performances level toward product qualities. In addition, customer price sensitivities also asked to get information about potential loss sales to projected revenue if price rising is stated. This research results that 2nd semester (July-December 2007) is the most efficient, and the most effective promotion media are televisions, magazines, promotion events, and newspapers. This research also notes that friends or families are the prime information source for customers to know about ISP X. In order to improve the recent qualities, here are given some qualities atributes that urgently need according to customers to be fixed. In other side, it also noted that customers are somewhat price-sensitive. However, better offer from competitor still looks more risky than price rising issue itself, though with better qualities present.